2020 Global report on food crises: Joint analysis for better decisions: September update in times of COVID‑19 - Food Security Information Network; Global Network Against Food Crises; Vos, Rob (Food and Agricultural Organization of the United Nations, 2020)
The GRFC 2020 reported the highest global number of acutely food-insecure people on record. It revealed that in 2019, some 135 million in 55 countries and territories were in need of urgent food, livelihood and nutrition assistance as a result of conflict, weather extremes, economic shocks, or a combination of all three drivers. This figure reflected not only worsening levels of acute food insecurity in many countries, but also the wider availability of food security data, including in previously inaccessible areas or in contexts that had previously yielded poor-quality data. In these 55 food crisis countries and territories, an estimated 75 million children were stunted and 17 million were suffering from acute wasting. Food insecurity and limited access to well functioning health, WASH and social protection systems increase the risk of malnutrition for the most vulnerable. This GRFC 2020 September update in times of COVID‑19 provides acute food insecurity data for 26 countries identified in the GRFC 2020 and also includes Togo in the report for the first time. The cut-off date for the information and data used to prepare this report was 30 September 2020.